Effectiveness and safety of tacrolimus therapy for myasthenia gravis: A single arm meta-analysis. (May 2019) - Wang, Liang; Xi, Jianying; Zhang, Suxian; Wu, Hui; Zhou, Lei; Lu, Jiahong; Zhang, Tiansong; Zhao, Chongbo
Highlight: This single arm meta-analysis demonstrates that tacrolimus may be a beneficial drug option to myasthenia gravis. Tacrolimus therapy exhibits a steroid-sparing effect in myasthenia gravis treatment. Disease duration of myasthenia gravis may be correlated with the clinical improvement after tacrolimus therapy. Abstract: To evaluate the effectiveness and safety of tacrolimus in myasthenia gravis (MG) patients, a systematic review and meta-analysis was performed. Researches published between January 1, 2000 and December 31, 2017 in English language were searched in Medline, Embase, Cochrane Central Register of Controlled Trials (CENTRAL) andclinicaltrials.gov databases. We extracted the outcome measures regarding the dose of glucocorticoids (GC), Myasthenia Gravis Foundation of America (MGFA) quantitative myasthenia gravis score (QMGS), MG activities of daily living (MG-ADL) and serum anti-acetylcholine receptor (AChR) antibody titer in each included study. Among 25 studies involving 633 patients, we observed a mean reduction in GC dose by 1.21 (95% CI, 0.44–1.98), QMGS by 2.02 (95% CI, 0.86–3.18), MG-ADL by 1.21 (95% CI, 0.81–1.62) and serum anti-AChR antibody titer by 0.61 (95% CI, 0.43–0.80), which all reached a statistical significance (p < 0.01). Interestingly, a significant correlation was acquired between the disease duration and the reduction of QMGS (p = 0.033; 95% CI, −0.64 to −0.033). Adverse events (AEs) were recorded in 258 of 633 patients (40.8%) with tacrolimus therapy while most were mild. Our meta-analysis demonstrates that tacrolimus may be a beneficial drug option to treat MG.